2023
DOI: 10.1002/eap.2927
|View full text |Cite
|
Sign up to set email alerts
|

Forest restoration treatments indirectly diversify pollination networks via floral‐ and temperature‐mediated effects

Cora B. Davies,
Thomas Seth Davis,
Terry Griswold

Abstract: In North American conifer forests a variety of federally initiated thinning programs are implemented to restore pre‐European settlement forest structures, but these changes may impact ecosystem function via impacts on sensitive biotic communities. Across the wildland‐urban interface of the Front Range region of Colorado, agencies associated with the ‘Collaborative Forest Landscape Restoration Program’ (CFLRP) have implemented thinning treatments across thousands of hectares of ponderosa pine forest; here we le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Lettow et al (2018) found thinning coupled with controlled burns, significantly increased pollinator richness and abundance in oak savannas relative to unmanaged controls. Other studies observed similar results (Rivers et al, 2018;Glenny et al, 2022;Davies et al, 2023). Alternatively, at some sites, the removal of non-native plants may provide less nesting habitat for stem or cavity-nesting bees (Tonietto and Larkin, 2018).…”
Section: Mechanical and Hand Thinningmentioning
confidence: 70%
“…Lettow et al (2018) found thinning coupled with controlled burns, significantly increased pollinator richness and abundance in oak savannas relative to unmanaged controls. Other studies observed similar results (Rivers et al, 2018;Glenny et al, 2022;Davies et al, 2023). Alternatively, at some sites, the removal of non-native plants may provide less nesting habitat for stem or cavity-nesting bees (Tonietto and Larkin, 2018).…”
Section: Mechanical and Hand Thinningmentioning
confidence: 70%